Development of Basketball Physical and Technical Test Instruments: Validity and Reliability Analysis - Patriana Nurmansyah Awwaludin; Masayu Rizka Risjanna; Muhammad Naufal Abdurahman; Mona Fiametta Febrianty (Department of Physical Education, Faculty of Health Sciences, Universitas Jenderal Soedirman, 2025)
The development of measurement instruments for basketball skills and physical performance is essential to support athlete training programs based on systematic and data-driven approaches. Although basketball in Indonesia has grown steadily, the transition from amateur to professional levels still faces challenges, one of which is the absence of standardized measurement tools that are both valid and reliable across different stages of athlete development. This study aimed to develop and examine the validity and reliability of basketball skill and physical test instruments intended for athletes aged 12–18 years. A quantitative methodological approach was employed, focusing on content validation through expert judgment. The validation process involved ten experts in basketball and sport science who assessed the relevance of each test item. Content validity was analyzed using the Content Validity Ratio (CVR), while inter-rater reliability was examined with Fleiss’ Kappa. The results indicated that of the 11 skill test items, 7 were valid and reliable, with coefficients ranging from moderate to almost perfect. However, several items, such as passing version II, right- and left-hand dribbling, and speed dribbling shoot, were deemed invalid and showed low reliability (slight). In the physical test domain, 8 of 10 items were validated and demonstrated almost perfect reliability, while the standing long jump and hexagon test were found invalid and yielded low reliability (poor). These findings suggest that the developed instruments meet validity and reliability standards for most items, and thus hold potential as reference tools for assessing physical and technical performance in youth basketball. Furthermore, the instruments provide a foundation for future studies involving field trials to confirm their effectiveness in athlete development programs.